Motherhood and Schizophrenia: A Critical Review - Murray, Polly (2009)
Historically, society has developed the notion of a mother as a submissive, caring and responsible figure; in contrast to stereotypes of people diagnosed with schizophrenia, which evoke connotations with danger, violence and irrationality.